A Learning for Gifted and Talented Students in Islamic Education - Gulzhaina K. Kassymova; Mustafa Tevfik Hebebci; Mutathahirin Mutathahirin; Yerassyl K. Talgatov (Khalifa Journal of Islamic Education, 2025)
The research aims to analyze suitable learning approaches for gifted and talented students at school. A qualitative method with a "single-case embedded design (multiple units of analysis)" was used for this study. Data were collected from 10 informants, including 3 management team members, 3 experienced teachers, and 4 students enrolled in the exemplary education program. Data analysis was conducted thematically using the interactive model by Miles & Huberman, assisted by Nvivo 12 software. The results indicate six learning strategies i) depth and critical learning, ii) innovation learning, iii) question critical issue, iv) competition learning, v) exploration learning, and vi) experience learning. The findings suggest that learning for gifted and talented students should provide opportunities and freedom for exploration to maximize their potential independently, supported by creative and innovative teacher guidance. Therefore, it is crucial to develop specific learning approaches that consider the characteristics of gifted and talented students. Additionally, teachers must continually enhance their skills to support learning that meets the needs of these students. School, parents, and the community must collaborate to create a learning environment that maximizes the potential of gifted and talented students.